A novel semi-active piston-TLCD for structural vibration control: Design, modeling, and performance assessment - Navdar, Muhammet Burhan; Celebi, Erkan; Engin, Tahsin; Kemerli, Muaz; Serbes, Sefer Arda; Iric, Sedat; Metin, Muzaffer; Faizan, Abdul Ahad (ELSEVIER SCI LTD, 2026)
This study presents the development, modeling, and experimental testing and verification of a novel semi-active Tuned Liquid Column Damper (SP-TLCD) system equipped with an externally mountable electromagnetic dualpiston brake mechanism. The system enables real-time modulation of damping properties without requiring structural modifications to conventional TLCD units and uniquely supports both damping-based and force-based control strategies. Structurally simple, cost-effective, and easily integrable SP-TLCD is addressed including the practical challenges such as actuator failures and time delays to enhance real-time control performance. The mechanical configuration, operational principles, control algorithms, and mathematical modeling of the proposed system are introduced. Its vibration mitigation performance was assessed through shake table experiments and validated numerical simulations on a slender single-degree-of-freedom (SDOF) frame subjected to broadband (earthquake) and narrowband (colored noise) excitations. Control strategies designed without considering time delay, both damping- and force-based, showed comparable RMS performance, highlighting the system's flexibility to accommodate multiple semi-active control schemes. Even under single-piston operation, the system retained 84.4 % of its full-capacity response, demonstrating resilience under partial failure. Furthermore, a timedelay-compensated strategy developed using Genetic Algorithm (GA) optimization achieved an average 30 % reduction in RMS response, corresponding to 91 % of the ideal delay-free case and outperforming the conventional LQRCC by 25 %. These results demonstrate that the proposed system can operate stably and efficiently in real-time applications by addressing practical constraints. Overall, the SP-TLCD offers a valuable addition to literature with its compatibility with various control strategies, modular design, external mountability, and demonstrated potential for effective vibration mitigation.
Keywords: Tuned liquid column damper (TLCD); Semi-active vibration control; Real-time structural control; Time-delay control; LQR clipping control; Experimental investigation; Discrete-time state-space model; Genetic algorithm (GA); Particle swarm optimization (PSO); LIQUID COLUMN DAMPERS; CONTROL STRATEGY; TIME-DELAY; ABSORBER; FEEDBACK; SYSTEMS; Engineering; Geology